ANALYSIS OF MODALITY METAPHORS IN STUDENT TRANSLATIONS ON THE TOPIC OF PRIVATE HOSPITALS BEING BETTER THAN STATE HOSPITALS IN TERMS OF SERVICES (SYSTEMIC FUNCTIONAL LINGUISTIC APPROACH) - Bambang Abdul Syukur; Dessy Dwijayanti; Ramadan Adianto Budiman (Acceleration: Multidisciplinary Research Journal, 2024)
This study is a qualitative descriptive study that aims to analyze the types of modality metaphors and their translation techniques in argumentative texts written by students of the Midwifery Undergraduate Program. This study uses the Systemic Functional Linguistics (SFL) approach, and the data is analyzed using the content analysis method to identify the types of modality metaphors and the translation techniques used. The results of the study indicate that the most dominant type of modality metaphor is probability modalization, while bond modulation is not found. The three translation techniques applied are common equivalents (96 times), modulation (3 times), and linguistic amplification (1 time). In terms of translation quality, the aspects of accuracy, acceptability, and readability reached an average of 83%, with an overall average value of 2.03.